PEMANFAATAN APLIKASI WHATSAPP GROUP SEBAGAI MEDIA PEMBELAJARAN DARING PADA MATA KULIAH ULUMUL HADIS - Maula, Atika Rofiqatul; Muqowim, Muqowim; Aula, Siti Khodijah Nurul; Ridhaeva, Haqan (Balai Diklat Keagamaan Jakarta, 2023)
Abstract WhatsApp is one of the most practical social media. The ease of use and completeness of features of the application can be used as a learning media at various levels of education, including lectures. This research examines student satisfaction with the WhatsApp Group (WAG) use as learning media in the Ulumul Hadith course. This type of research is quantitative descriptive. Data was obtained from a survey distributed to 73 students using Google Forms. The survey found that 94.5% of students stated that Ulumul Hadith's lectures using WAG media are elementary to follow, and 84.9% answered that using WAG as a learning medium increased student motivation. Furthermore, the survey finds that 63% of students are